Sustainable technology in developed countries: waste municipal management - Hoareau, Carol Emilly; Noraziah, Ahmad; Maria, Nuid; Rubiyatno, .; Khoi, Dao Nguyen; Kristanti, Risky Ayu (2021)
As more studies were conducted and global events unfold, a greater emphasis is being placed on the importance of preserving the Earth's natural resources and cycles before we face a catastrophic climate crisis. Thus, developed countries are constantly adapting their policies and legislation to promote green development for the sake of sustainable development, which benefits both the environment and the socioeconomic segment. As populations grow and living standards improve, more waste is generated. Appropriate municipal waste management is necessary to avoid harm to the environment, wildlife, and human health. Sustainable municipal solid waste management is even included in the United Nations' (UN) Sustainable Development Goals, which aim to improve the world's environment and economy. The European Union (EU) member states' waste management systems can be considered exemplary. In some countries, landfills have been prohibited, promoting the use of more sustainable technologies such as organic waste incineration, recycling, and composting. However, a divide exists between member countries, with some lagging behind in terms of waste management strategies. Thus, this paper examined the current state of municipal waste in EU member states, followed by a review of the various disposal technologies implemented. The difficulties and environmental concerns that must be overcome are discussed, as are the recommendations and possible future directions.